Cationic nanomicelles derived from Pluronic F127 as delivery vehicles of Chinese herbal medicine active components of ursolic acid for colorectal cancer treatment. Issue 29 (27th April 2018) - Yan, Zhaokun; Wang, Qingtang; Liu, Xiaolong; Peng, Jun; Li, Qin; Wu, Ming; Lin, Jiumao
Abstract : A cationic nanomicelle derived from Pluronic F127 as a delivery vehicle of ursolic acid for enhanced colorectal cancer treatment. Abstract : Ursolic acid (UA) has shown great potential in cancer therapy but their efficacy is seriously compromised by poor water-solubility and limited cellular uptake. In this paper, cationic nanomicelles self-assembled from Pluronic F127 with the cationic polymer of C18 -polyethylenimine (C18 -PEI) as a functional component are fabricated as delivery vehicles of Chinese herbal medicine active components of ursolic acid (UA) for colorectal cancer treatment. The inhibition effects of this drug loaded cationic nanomicelles (named as FUP) on cell viability and cell colony formation were more significant than the free UA, due to their cationic surface which can increase UA uptake by colorectal cancer cells. Cell cycle analysis showed that this inhibition effect was mediated by a cell cycle arrest at the G1 checkpoint, and the cell death induced by these nanomicelles occurred via apoptosis, which was detected by annexin V antibody and propidium iodide staining. Further western blot analysis demonstrated the apoptosis mechanism was associated with the regulation of Fas/FasL and activation of caspase-8 and caspase-3. Therefore, our cationic nanomicelles can potentially be used to enhance the therapeutic effect of UA for colorectal cancer treatment.